2015
DOI: 10.3390/agriculture6010002
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber Rhizosphere Microbial Community Response to Biocontrol Agent Bacillus subtilis B068150

Abstract: Gram-positive bacteria Bacillus subtilis B068150 has been used as a biocontrol agent against the pathogen Fusarium oxysporum cucumerinum. Cucumber was grown in three soils with strain B068150 inoculated in a greenhouse for 90 days, and the colonization ability of strain B068150 in cucumber rhizosphere and non-rhizosphere soils was determined. Changes in total bacteria and fungi community composition and structures using denaturing gradient gel electrophoresis (DGGE) and sequencing were determined. Colony count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Surprisingly, Bacillus abundance was significantly decreased rather than increased, which was also observed in other studies. 15,60,61 Some BCA (including Bacillus subtilis) do not maintain substantial colonization on plant roots over time, however, there are native microbes that can significantly improve the maintenance of Bacillus subtilis. 62 This kind of reverse impact also addresses the interactions between BCA and indigenous microbes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, Bacillus abundance was significantly decreased rather than increased, which was also observed in other studies. 15,60,61 Some BCA (including Bacillus subtilis) do not maintain substantial colonization on plant roots over time, however, there are native microbes that can significantly improve the maintenance of Bacillus subtilis. 62 This kind of reverse impact also addresses the interactions between BCA and indigenous microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus and Trichoderma species are the most commonly used effective biocontrol agents against a broad spectrum of root, shoot, and postharvest pathogens. 12,13 High-throughput sequencing can provide a better picture of the complex and diverse soil microbial communities with high accuracy and reasonable cost compared to traditional methods such as T-RFLP, 14 DGGE, 15,16 qPCR. 17,18 Therefore, this study aimed to determine whether the treatment of ginger with commercially available BCA (Bacillus subtilus and Trichoderma harzianum) alters the community structure of the rhizospheric microorganisms using the 16S rRNA gene profile.…”
Section: Introductionmentioning
confidence: 99%
“…And the sequence data was subsampled to equal sequencing depth for each sample. Operational taxonomic units (OTUs) with 97% similarity cutoff (Li et al, 2016) were clustered and chimeric sequences were identified and removed using UPARSE (version 7.1 1 ). The taxonomy of each OTU representative sequence was analyzed by RDP Classifier 2 against the 16S rRNA database (Silva 132/16S_bacteria) and ITS database (unite7.2/its_fungi) using confidence threshold of 0.7, relative abundance below 1% were combined as others.…”
Section: Soil Dna Extraction Pcr Amplification and Illumina Sequencingmentioning
confidence: 99%
“…Cucumber (Cucumis sativus L.) is one of the most common vegetables worldwide, many studies reported that strains such as Bacillus subtilis, Bacillus amyloliquefaciens, and Pseudomonas spp. affect soil microbial community in the cucumber rhizosphere (Yamamoto-Tamura et al, 2011;Li et al, 2016;Qin et al, 2017), however, as a promising sources of biocontrol agents, how Streptomyces affect soil microbial community in cucumber rhizosphere remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are many bacterial and fungal species that can function as PGPM, of which Bacillus members are well-described in the literature for successfully promoting plant growth in diverse ways. Bacillus isolates colonize host plant roots and promote plant growth by producing bio compounds, such as the hormone indole-3-acetic acid (IAA), as well as spermidine and 2,3-butanediol [4,8,9], by defending against pests and pathogens by producing antibiotic substances such as hydrogen cyanide (HCN), chitinase, and siderophores [10][11][12], and by competing for nutrients and micro-niches, as well as induction of plant resistance [13][14][15]. Some studies have reported on the synergistic and antagonistic effects of PGPM, as well as other microorganisms within the rhizosphere and beyond (in bulk soil), which could indirectly facilitate plant growth [16][17][18].…”
Section: Introductionmentioning
confidence: 99%